X-Ray Computed Tomography versus Metallography for Porosity Analysis in Aluminium RPT Castings - Malisano, J; Kumar, S; Lui, C; O'Reilly, K (2017)
X-Ray Computed Tomography (XCT) is compared with metallography for the evaluation of the size, morphology, and distribution of pores in Al-Si Reduced Pressure Test castings (RPTs) in 3D and 2D, respectively. The results showed that porosity assessment in 3D was more effective than in 2D, due to the highly connected pore structure that forms in RPTs which cannot be adequately represented by the latter technique. The uncertainty in the 3D measurements that is introduced by sub-voxel pore features was shown to have a significant impact on the accuracy of the analysis, but even so it compared better to that determined by the Archimedes’ principle than the 2D technique for evaluating the fraction of porosity in the samples.